Signing of technology transfer and licensing agreement between IITA and HARVESTFIELD INDUSTRIES LIMITED - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Signing of Technology Transfer and Licensing Agreement between IITA and HARVESTFIELD INDUSTRIES LIMITED for the manufacturing and distribution of Aflasafe in Nigeria​